Fachkräfte für die Entwicklung Fortbildungskooperationen zwischen Ghana undden beiden deutschen Staaten, 1956-1976 - Otto, Jana (Studien zur Internationalen Geschichte, 2022)
After its independence in 1957, Ghana sent specialists to both German states for professional education and training. This transnational entanglement history takes various perspectives to analyze the goals that Ghana, the FRG, and the GDR pursued with these programs during the Cold War and their respective development plans. It also takes into account the interests of Ghanaian specialists and the freedom they had to make their own decisions.